Exploring the genetic causal association of TIMP3 on CKD and kidney function: a two-sample mendelian randomization - Chen, Huang; Chen, Lixun; Chen, Yufeng; Guo, Qinyu; Lin, Shirong (Frontiers in Genetics, 2024)
Background:Numerous studies have demonstrated a positive association between the level of tissue inhibitor of metalloproteinase 3 (TIMP3) and chronic kidney disease (CKD).Nevertheless, whether those associations reflect causal links still to be determined. This study intended to research the causal relationship of TIMP3 with CKD and markers of kidney function,such as creatinine-based estimated glomerular filtration rate (eGFRcrea), cystatin C-based estimated glomerular filtration rate (eGFRcys), eGFRcrea in diabetics(eGFRcrea(DM)) and eGFRcrea in non diabetics(eGFRcrea(No DM)).Methods:In this study, we investigated the causal relationships between TIMP3 and CKD and kidney function markers using a two-sample Mendelian randomization (MR) technique.We used summary level datasets for TIMP3 and CKD from genome-wide association studies that we were able to access through the study by Suhre K and Pattaro C.Results:We found that TIMP3 had a significant positive causal effect on the risk of CKD (Inverse variance weighted (IVW):odds ratio (OR):0.962, 95% confidence interval(CI):(0.936-0.988),P:0.005) .However TIMP3 levels had no significant effect on risk of eGFRcys (PIVW: 0.114) ,eGFRcrea(PIVW:0.333).After grouping patients based on their diabetes status, we found that genetically higher levels of TIMP3 had a significant impact on eGFRcrea in participants without diabetes 2 (OR:1.003,95%CI:(1.001-1.006),P IVW:0.007 ),but not in participants with diabetes(PIVW= 0.057).Heterogeneity and pleiotropy analyses were carried out to verify the accuracy of the MR findings.Their findings were all not statistically significant.Our study suggests that TIMP3 may be causally associated with CKD and eGFRcrea(No DM)in people of European ancestry. Strategies aimed to increase TIMP3 levels may provide new ways to delay the deterioration of renal function.